The Concern for the Widow and the Fatherless in the Ancient Near East: A Caste Study in Old Testament Ethics - Havice, Harriet K. (1978)
Diss.; Order No. 7915827; also on Syria, Mesopotamia, Egypt; Diss Abstr 40 (1979-80) 314-A.